(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Mistry is an influential chronicler of modernpublic among political life. Within this study, we be providing the remarkablefeature of his fiction is toward it captures the crowded throbbing life ofIndia. Such a Long trip, apart as of many further things, presents a realisticimage of Indian society. “Mistry manages toward conveying a vivid image ofIndia, although sharp affectionate sketches of Indian relation life among agift pro erotic satire.” This novel portrays diverse facets of Indiansocioeconomic life as well as Parsi Zoroastrian life, customs among religion.Rohinton Mistry‘s works seeks toward evolve a vision toward involves both thegroup of people -centered existence of the Parsis among their involvement viathe wider national framework. His novels are concerned via the experience ofthe Parsi within India. Mistry, re-narrates the history of his group of peopleamong nation as it has been inside of the post-Independence period. Thisreparation of history inside of a way portrays cognizance of tensions amonggoals, hazards among issues of presence of individual, open among nationalissues. Mistry has, inside of this sense, effectively abused some authenticpurposes of post-Independence period among attempted toward reexamine themamong re-describe about his group of people among country through the variousnarratives woven within the novel.